ANALISIS PENYAJIAN LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA PT. BANGUN BANGKA BERSAMA - Kurniati, Stefanni; Medinal; Novika (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This research is a qualitative research with a descriptive approach using primary data obtained from interviews and observations and using secondary data from journals, books and similar previous studies. The data collection techniques used are interviews and documentation of the data needed in this case, namely the financial sreports of PT Bangun Bangka Bersama. The results showed that the financial statements of PT Bangun Bangka Bersama were not in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) as evidenced by the number of financial statements that were not presented and the financial statements presented were not in accordance with SAK ETAP. The reports presented are only the statement of financial position and income statement while the statement of changes in capital, cash flow statement and notes to the financial reports are not presented.